2015
DOI: 10.1038/leu.2015.179
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of BCL-2 proteins efficiently induces apoptosis in progenitor cells of high-risk myelodysplastic syndromes patients

Abstract: Deregulated apoptosis is an identifying feature of myelodysplastic syndromes (MDS). Whereas apoptosis is increased in the bone marrow (BM) of low-risk MDS patients, progression to high-risk MDS correlates with an acquired resistance to apoptosis and an aberrant expression of BCL-2 proteins. To overcome the acquired apoptotic resistance in high-risk MDS, we investigated the induction of apoptosis by inhibition of pro-survival BCL-2 proteins using the BCL-2/-XL/-W inhibitor ABT-737 or the BCL-2-selective inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 59 publications
(98 reference statements)
4
84
0
1
Order By: Relevance
“…Interestingly, although Mcl-1 had previously been shown to confer resistance to ABT-737 and ABT-199 in other hematological malignancies and solid tumors, 10,[18][19][20]43,44 its role in mediating resistance in CLL had remained somewhat controversial. For example, in the study of Vogler et al, 15 induction of Mcl-1 expression by stimulation with interleukin-4 or interferon-g was associated with only marginal protection, prompting the authors to conclude that resistance to ABT-737 in CLL is largely Mcl-1 independent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, although Mcl-1 had previously been shown to confer resistance to ABT-737 and ABT-199 in other hematological malignancies and solid tumors, 10,[18][19][20]43,44 its role in mediating resistance in CLL had remained somewhat controversial. For example, in the study of Vogler et al, 15 induction of Mcl-1 expression by stimulation with interleukin-4 or interferon-g was associated with only marginal protection, prompting the authors to conclude that resistance to ABT-737 in CLL is largely Mcl-1 independent.…”
Section: Discussionmentioning
confidence: 99%
“…17 Previous studies by our group have shown that sustained engagement of the BCR induces Mcl-1, 6 and high levels of Mcl-1 were shown to inversely correlate with treatment response in the phase 1 study of ABT-263 in CLL. 12 In addition, high levels of Mcl-1 have been shown to protect other hematological malignancies and certain solid tumors from ABT-199, [18][19][20] suggesting that Mcl-1 could also confer ABT-199 resistance to CLL cells. To further explore this possibility, we evaluated whether BCR-induced Mcl-1 overexpression can protect CLL cells from ABT-199 and whether this protection can be overcome by available BCR signaling inhibitors.…”
mentioning
confidence: 99%
“…In a transgenic model of MDS progressing to AML, treatment with ABT-737 reduced bone marrow blasts and progenitor cells by increasing apoptosis and significantly extended lifespan (113). Jilg et al demonstrated that inhibition of BCL-2 and BCL-X L with ABT-737 or specific inhibition of BCL-2 with venetoclax was toxic to bone marrow cells from high-risk MDS and secondary AML patients, whereas cells from low-risk MDS and normal, age-matched bone marrow remained largely unaffected (114). Sensitivity to ABT-737 and venetoclax was observed in samples from treatment-naïve and treatment failure patients, suggesting that the effects of BH3 mimetics depend primarily on the level of mitochondrial priming irrespective of prior treatment.…”
Section: Future Considerations and Conclusionmentioning
confidence: 99%
“…Similarly, overexpressed Mcl-1 can also be responsible for ABT-263 and ABT-199 resistance in CLL cells. In fact, high levels of Mcl-1 inversely correlated with treatment response in the phase I study of ABT-263 [25] and protected hematological malignancies from ABT-199 [33, 34]. …”
Section: Introductionmentioning
confidence: 99%